2006
DOI: 10.1159/000096105
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Terahertz Pulsed Imaging with Transmission Microradiography for Depth Measurement of Enamel Demineralisation in vitro

Abstract: Terahertz pulsed imaging (TPI) is a relatively new, non-ionising and non-destructive imaging technique for studying hard tissues which does not require tooth section preparation, unlike transmission microradiography (TMR). If TPI can measure the depths of caries/demineralisation lesions accurately the same tooth samples could be reused and remeasured during in vitro and in situ studies on de- and/or remineralisation. The aim of this study was to compare TPI and TMR for measuring the depths of a range of artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 41 publications
0
30
0
1
Order By: Relevance
“…Optical methods appear to offer a reliable assessment of pulp vitality. Much work has already been carried out in the field of imaging and caries localization by throughput of light with an emphasis on the determination of suitable transmission windows in the IR and THz spectral ranges [7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Optical methods appear to offer a reliable assessment of pulp vitality. Much work has already been carried out in the field of imaging and caries localization by throughput of light with an emphasis on the determination of suitable transmission windows in the IR and THz spectral ranges [7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Crawley et al [165] showed that areas of demineralized and hypomineralized enamel can be discriminated from sound tissue in TPI images. The depth of artificial surfacesoftened lesions created in enamel using an acid gel measured by TPI compared well with measurements [167]. These methods appear best suited for measurement of the lesion depth and the remaining enamel thickness for erosion measurements.…”
Section: Ultrasound and Terahertz Imagingmentioning
confidence: 74%
“…Thus, the slow-freeze, slow-thaw cycle will reduce the THz contrast in cases such as muscle-fat comparisons as the refractive index of the muscle will become lower and therefore closer to that of the fat. However the contrast will be improved in cases where the biomedical material of low water content has a higher refractive index such as enamel (n = 3 at 1 THz [8]): in such cases, after the freeze-thaw process, the muscle will have a lower refractive index and so the difference between the muscle and enamel will be greater. Thus, for inhomogeneous samples, it will depend on the composition of the inhomogeneities as to whether the contrast will be reduced or enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed interesting uses of THz waves such as to delineate cancer margins [2][3][4], monitor the water content in living plants [5,6], and detect dental defects [7,8].…”
Section: Introductionmentioning
confidence: 99%